Preliminary study of airflow and heat transfer in a cold room filled with apple pallets: Comparison between two modelling approaches and experimental results. (5th February 2015) - Hoang, Hong-Minh; Duret, Steven; Flick, Denis; Laguerre, Onrawee
Abstract: Two CFD modelling approaches of transient heat transfer by forced convection in a cold room filled with four apple pallets have been performed and compared with experimental data. For the first approach, each apple pallet is considered as one porous medium block. For the second, each pallet is considered as 8 solid blocks representing the apple bins. The numerical results obtained by these two approaches show a good agreement with the experimental results regarding air velocity and product temperature evolution during cooling process. A better prediction of product temperature evolution is obtained with the solid block approach. The porous medium approach gives a fairly good result with a much smaller mesh numbers (nearly 4 times) than the solid block approach. Four turbulence models (standard k – ɛ, RNG k – ɛ, realizable k – ɛ, and shear stress transport SST k – ω ) and two heat transfer models for porous medium (local thermal equilibrium and local thermal non-equilibrium model) are tested to determine the most appropriate ones for the studied configuration. Highlights: Forced convection in cold room with apple pallets is studied by 2 CFD approaches. 1st Approach: each pallet is considered as one porous medium (PM) block. 2nd Approach: each pallet is modelled as 8 solid blocks (SB). Numerical results show a good agreement with the experimental results. PM approach gives good results with mesh numbers 4 times smaller than SB approach.